Preparation method of novel nickel-aluminum composite material and method for preparing hydrogen and carbon nanotubes
Through the preparation of the new nickel-aluminum composite catalyst, the problem of the existing technology being difficult to achieve high conversion rate hydrogen production and high yield preparation of high-quality carbon nanotubes at the same time is solved, and the synchronous preparation of high-efficiency hydrogen production and high-quality carbon nanotubes is achieved, reducing the cost of hydrogen production and improving the performance of carbon nanotubes.
Patent Information
- Application Number
- CN202510148924.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-04-15
AI Technical Summary
The existing catalyst technology is difficult to achieve high conversion rate hydrogen production and high yield carbon nanotube production at the same time, and the quality of the prepared carbon nanotubes is poor, making it difficult to meet the demand of the battery market.
Using the new nickel-aluminum composite material as a catalyst, carbon nanotubes with high catalytic activity and high added value were prepared through clean activation of aluminum plates, multi-stage oxidation, chemical deposition and acidic amplification-alkaline mold release treatment.
The high conversion rate of methane cracking and high yield of hydrogen production are achieved, which reduces the cost of hydrogen production and improves the conductivity and uniformity of the tube diameter distribution of carbon nanotubes, which is suitable for the low-cost preparation and promotion of new energy batteries.
Smart Images

Figure CN119824506A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of novel nano material preparation, and in particular to a method for preparing a novel nickel-aluminum composite material and a method for preparing hydrogen and carbon nanotubes. Background Art
[0002] Methane is the main component of natural gas and biogas, and its reserves and sources are relatively abundant in my country. Methane catalytic cracking technology can solve the fossil energy crisis while reducing or even avoiding the generation of CO2 to produce green hydrogen energy in a more environmentally friendly way. At present, the main difficulty hindering the industrial application of methane cracking hydrogen production is that the cost of methane hydrogen production is still relatively high. In the process of methane catalytic cracking process moving towards industrialization, catalyst technology innovation will play a decisive role. At present, the published catalyst technology has a lot of research on catalytic cracking hydrogen production or catalytic cracking carbon tube production, but there are few introductions to composite catalysts that take into account both high methane conversion rate hydrogen production and high yield carbon tube production. Using high-value-added carbon nanotubes to effectively compensate for the cost of hydrogen production will significantly reduce the cost of methane cracking hydrogen production and form a significant cost advantage over traditional hydrogen production processes such as water electrolysis.
[0003] Patent CN110721691A uses Ca2Fe y Al 2-y O5 loaded with Ni x Fe 3-xNanoparticles, a new catalyst material is prepared, which maintains high catalytic activity and stability in the process of methane cracking and hydrogen production, with high methane conversion rate and good sustainability. However, nanocarbon with low graphitization degree is obtained, which is difficult to effectively compensate for the cost of hydrogen production; CN 115364890B discloses a simple impregnation method, that is, immersing the molecular sieve in an active metal salt solution such as nickel nitrate and iron nitrate for several hours, so that the active metal is loaded on the surface of the molecular sieve, thereby obtaining a catalyst with methane cracking activity. Using this catalyst, a carbon nanotube product with higher value can be obtained, but the amount of active metal loaded by this simple pore adsorption method is small, and the uniformity cannot be controlled. The prepared carbon nanotubes have the problems of thick tube diameter, many defective bends in the tube wall, and poor conductivity, which is difficult to meet the high-rate charge and discharge requirements of the battery market. Alumina is often used as a catalyst carrier because of its large specific surface area and rich pore structure. CN106102906B uses spherical, amorphous α-Al2O3 and γ-Al2O3 as carriers, and loads active metals by impregnation / coating to obtain a catalyst that can be used for the preparation of carbon nanotubes. However, as described in the patent, the porous alumina material has no regular appearance and pore structure, so it is difficult to play the role of the template constraint. The active metal is attached to the outer surface of the support body with a large size of 100nm, which is not conducive to the preparation of small-diameter high-performance carbon nanotubes. Moreover, the catalyst is only suitable for the catalytic cracking of ethylene with relatively weak bond energy, and the catalytic activity of methane is not introduced. The experimenters in this group repeated the catalyst preparation process and used it in the methane cracking experiment, but there was no obvious catalytic effect. Ethylene and propylene are deep-processed products of fossil energy. Not only are their prices much higher than methane and natural gas, but they are also contrary to the original intention of green hydrogen production.
[0004] In summary, how to design a new catalyst that can take into account both high conversion rate of methane cracking to produce hydrogen and high yield of carbon nanotubes will be of great significance to the field of energy utilization, especially the field of clean hydrogen production, and even the low-cost preparation and promotion of new energy batteries. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention proposes a method for preparing a novel nickel-aluminum composite material, which can obtain a composite material for preparing hydrogen and carbon nanotubes; at the same time, the present invention also provides a method for simultaneously preparing hydrogen and carbon nanotubes, which has a high economic value.
[0006] The technical solution is as follows: A method for preparing a novel nickel-aluminum composite material, characterized in that it comprises the following steps: (1) Cleaning and activation of aluminum plates: The recycled aluminum is pretreated using the process steps of “polishing-waxing-alkali washing-acid washing”; (2) Multi-stage oxidation: The activated aluminum plate pretreated in step (1) is used as the anode, and a metal plate including a nickel plate and a lead plate is used as the cathode, and a constant voltage pulse treatment is performed in an electrolyte; (3) Chemical deposition: The aluminum oxide plate prepared in step (2) is immersed in a solution containing nickel ions to perform a liquid phase chemical plating reaction: (4) The plate obtained in step (3) is subjected to an "acid expansion-alkaline stripping" treatment, filtered and washed until neutral, to obtain a gray powder, which is then dried and calcined to obtain a nickel-aluminum composite material.
[0007] The method is further characterized in that, in step (1), polishing: using an abrasive belt and a polishing paste to grind and polish the oxide film on the surface of the aluminum material; Wax removal: ultrasonic treatment of aluminum in an aqueous solution of a wax remover; Alkaline washing: adjust the pH of the aqueous solution of Na2OH, wash with ultrasound for 10 seconds, and then quickly transfer to pure water; Acid washing: At room temperature, use a mixed acid solution of phosphoric acid and nitric acid, ultrasonically wash for 30 seconds, then quickly transfer to pure water and rinse until neutral; In step (2), the electrolyte is a mixed aqueous solution of phosphoric acid and sulfuric acid, and H3PO4:H2SO4:H2O=1:4:45; reaction conditions: the reaction temperature is controlled to be 1-10°C; a constant voltage of 10-50V, an interval time of 1-20min, and a pulsed multi-stage oxidation reaction are used to achieve the effect of continuously refining the pore size of the porous layer of the oxide film during the repeated "generation-dissolution" process, and the oxidation level is controlled at 2-4 levels; In step (3), the chemical deposition solution comprises nickel ions, a fluorine-containing sensitizer, a carboxyl complexing agent, and a surfactant; the reaction conditions are: the reaction temperature is controlled to be 45-75°C; the reaction time is 1-10 minutes; and the solution pH is 3-7; In step (4), the acidic pore expansion uses a 5% phosphoric acid aqueous solution at a working temperature of 10-30°C and a reaction time of 1-2 minutes; the alkaline demoulding uses an alkaline solution including NaOH and NaCO3 at a working temperature of 30-50°C and a soaking reaction time of 10-60 seconds; the gray powder is dried at 80°C for 10 hours and calcined at 400-700°C for 4 hours to obtain a nickel-aluminum composite material.
[0008] A method for synchronously preparing hydrogen and carbon nanotubes using the above-mentioned nickel-aluminum composite material is characterized in that 0.01-1g of the nickel-aluminum composite material is weighed as a catalyst, placed in a quartz tube, preheated to 700°C, hydrogen and nitrogen mixed gas is introduced at a rate of 10-400ml / min, reacted for 5-30min, methane and nitrogen mixed gas is introduced at a rate of 100-1000ml / min, reacted for 20-60min, gas chromatography is used to perform real-time online detection of tail gas components at the end of the reactor, and the methane conversion rate is calculated; the carbon nanotubes generated in the reactor are collected, and the carbon nanotube generation rate is measured.
[0009] After adopting the present invention, a low-cost aluminum plate is used for cleaning and activation, and after multi-stage oxidation and chemical deposition treatment, an "acid expansion-alkaline demolding" treatment is used to finally obtain the required nickel-aluminum composite material. It is used as a catalyst, and hydrogen and methane are introduced to react, so that methane is cracked and converted into hydrogen, and carbon nanotube materials are obtained. The carbon nanotube material has high commercial value and is of great significance in the field of clean hydrogen production and even in the low-cost preparation and promotion of new energy batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 This is a flow chart of the preparation process of the nickel-aluminum composite material of the present invention; Figure 2 This is a scanning electron microscope composite image of the product after each process of Example 1 of the present invention (wherein a. primary oxidation; b. secondary oxidation; c. chemical deposition; d. carbon tube formation); Figure 3 The energy spectrum and element distribution diagram of the nickel-aluminum alloy catalyst prepared in Example 1 of the present invention; Figure 4 This is a photo of the carbon nanotubes prepared in Example 1 of the present invention; Figure 5 The actual photographs and scanning electron microscope photographs of the prepared film layers of Comparative Examples 1, 3, and 4 of the present invention (wherein a and b are the workpiece photograph and SEM of Comparative Example 1, respectively; c and d are the workpiece photograph and SEM of Comparative Example 3, respectively; e and f are the workpiece photograph and SEM of Comparative Example 4, respectively); Figure 6 This is a transmission electron microscope photo of the prepared carbon nanotubes in Comparative Example 2 of the present invention; DETAILED DESCRIPTION
[0011] See Figures 1 to 6 shown.
[0012] Example 1 A method for preparing a novel nickel-aluminum composite material comprises the following steps: (1) Cleaning and activation of aluminum plates: The recycled aluminum is pretreated using the process steps of “polishing-waxing-alkali washing-pickling”.
[0013] Polishing: Use 200-mesh and 1000-mesh sand belts respectively, and use the commercially available 3M 05973 polishing paste to grind and polish the oxide film on the surface of the aluminum; Wax removal: Set the temperature to 60°C and ultrasonically treat the aluminum material in a wax remover water solution (Dongguan Passivation Cleaning Technology Co., Ltd. 1002 type) for 5 minutes; Alkaline washing: Set the temperature to 50°C, adjust the pH of the Na2OH aqueous solution to 11, and then quickly transfer to pure water after ultrasonic washing for 10 seconds; Pickling: At room temperature, a mixed acid solution of phosphoric acid and nitric acid (H3PO4: HNO3: H2O = 1:1:18) is ultrasonically washed for 30 seconds and then quickly transferred to pure water and rinsed to neutrality. Using weak acid H3PO4 alone has low corrosion efficiency and requires heating treatment. Using nitric acid alone is easy to form a passivation film on the surface of aluminum, affecting the efficiency and effect of pickling. The combination of H3PO4 and HNO3 can improve the pickling efficiency at room temperature and obtain a smooth and bright base surface, which plays an important role in constructing an ordered pore structure in the subsequent process.
[0014] (2) Multi-stage oxidation: Electrode: The activated aluminum plate pretreated in step (1) is used as the anode, and the nickel plate, lead plate, etc. is used as the cathode; Electrolyte: A mixed aqueous solution of phosphoric acid and sulfuric acid (H3PO4: H2SO4: H2O = 1: 4: 45) is used. Using phosphoric acid alone will result in a membrane with large pore size and large pore distance, and cannot serve as a template. Using sulfuric acid alone can produce a membrane with a smaller primary pore size, but as an oxidizing acid, sulfuric acid has poor pore expansion and corrosion capabilities, and cannot dissolve the porous layer during the intermittent period, nor can it adjust the pore size and pore distance through multi-stage oxidation.
[0015] Reaction conditions: The reaction temperature is controlled at 5°C. The appropriate temperature can facilitate the formation of a uniform and continuous grinding film layer; a constant voltage of 30V, a primary oxidation time of 10min, an intermittent time of 5min, and a secondary oxidation reaction of 6min are used; when the power is on, an oxidation reaction occurs on the surface of the aluminum material to form an oxide film accompanied by the precipitation of hydrogen. When the power is off, a dissolution reaction occurs on the surface of the aluminum material, the porous layer on the upper layer of the oxide film is corroded, and the dense layer at the bottom has strong corrosion resistance and is retained, leaving continuous arc-shaped pits on the surface of the substrate. The bottom of the cavity is more easily punctured in the secondary oxidation stage, forming a new multi-porous channel structure, and gradually evolving into a new porous layer with finer pore size and higher array density. In the pulse oxidation process, the pore size is continuously refined by repeatedly undergoing the "generation-dissolution" process, and finally the pre-taken effect is achieved; the oxidation level should be controlled at 2-4 levels. Too few levels will not achieve the expected pore size, and too many levels will easily lead to pore connectivity, and even film rupture and collapse. (3) Chemical deposition: Weigh: 6g nickel acetate and 6g nickel fluoride, add into 1L deionized water, and measure Ni + Concentration 136ppm, F - Concentration 83ppm. Weigh 15g of citric acid and 0.3g of OP-10, add nickel solution and stir evenly, control the reaction temperature to 65℃; seal and react for 5min. By setting reasonable temperature and time, the reaction activity and deposition effect are improved, ensuring that the activity of fluoride ions is moderate, and the generated fluoride will not block the pores of the oxide film, allowing active ions to enter smoothly. Using active metal nickel ions, the catalytic cracking ability of methane is achieved. Different from the conventional impregnation reaction, which uses simple physical adsorption, the present invention activates the inner wall of the alumina pores and utilizes the attraction of opposite charges to pull active metal ions into the micro-nano pores with a larger specific surface area, thereby greatly increasing the number of active sites and having the ability to catalyze the cracking of methane.
[0016] Different from the conventional impregnation reaction, the chemical deposition solution configured in this method contains fluorine-based sensitizer nickel fluoride, or sodium fluoride, hydrofluoric acid, etc. The free fluoride ion concentration should be controlled at 50-500ppm. The use of fluoride ion sensitizer is the key to activate the inner surface of alumina pores, thereby increasing the active metal loading rate and the number of active sites. The main reasons for choosing fluoride ions as sensitizers are: 1. Fluoride ions are small in size and have a strong drilling effect; 2. Fluoride ions carry a negative charge, and are affected by the double charge layer at the interface between the substrate and the oxide film. The positively charged alumina pores have a pulling effect on fluoride ions; 3. After entering the pores, negatively charged fluoride ions can react with alumina, making the pores negatively charged, so that the active metal cations produce a positive pulling effect, making it easier for metal ions to enter the pores.
[0017] Different from conventional impregnation reactions, the chemical deposition solution configured in the present invention contains carboxyl compounds in citric acid. The addition of the complexing agent is another key to ensure that the catalyst has abundant active sites. The carboxyl compound forms a coating on the active metal ions in the form of complexation, forming a physical barrier between the deposited metal particles, improving the distribution uniformity of the metal particles, and reducing the probability of sintering during the roasting process, which is crucial to maintaining the nanometer size of the active metal particles. Different from conventional impregnation reactions, the chemical deposition solution prepared in the present invention contains an acid-resistant surfactant in the OP-10. The addition of the surfactant can make the inside of the pores hydrophilic, thereby improving the penetration efficiency of active metals.
[0018] (4) "Acidic pore expansion-alkaline demoulding" treatment: The plate obtained in step (3) is immersed in a 5% phosphoric acid aqueous solution, reacted at room temperature for 2 minutes, then transferred to pure water and rinsed to neutrality; the workpiece is immersed in a homemade alkaline demoulding agent LH003, the temperature is controlled at 50°C, and ultrasonic treatment is performed for 10 seconds before being removed. After bubbles appear on the surface of the workpiece, it is quickly rinsed with pure water and the detached fragments are collected. The collected product is dried at 80°C for 10 hours and calcined at 500°C for 4 hours to obtain a new composite material. Only alkaline solution is used for demoulding, and the alkaline solution corrodes the porous film layer from the outside to the inside.
[0019] A method for synchronously preparing hydrogen and carbon nanotubes using the nickel-aluminum composite material, weighing 0.05g of the composite material as a catalyst, putting it into a quartz tube with a diameter of 40mm, preheating it to 700°C, introducing hydrogen at a rate of 150ml / min, introducing nitrogen at a rate of 150ml / min, reacting for 5min, introducing methane at a rate of 200ml / min, introducing nitrogen at a rate of 100ml / min, and reacting for 30min. Use gas chromatography to perform real-time online detection of the tail gas components at the end of the reactor, calculate the methane conversion rate; collect and characterize the carbon nanotubes generated in the reactor, and measure the carbon nanotube generation rate.
[0020] Example 2 A method for preparing a novel nickel-aluminum composite material, the process adjustment is the same as that of Example 1, except that: Cleaning and activation of aluminum plate: (1) Acid cleaning: At 50°C, use a phosphoric acid aqueous solution (H3PO4:H2O=1:9), ultrasonically clean for 3 minutes, then quickly transfer to pure water and rinse until neutral.
[0021] (2) Multi-stage oxidation: Electrolyte: A mixed aqueous solution of phosphoric acid and sulfuric acid (H3PO4:H2SO4:H2O=1:9:90); Reaction conditions: The reaction temperature was controlled at 10°C.
[0022] Example 3 A method for preparing a novel nickel-aluminum composite material, the process adjustment is the same as that of Example 1, except that: (1) Multi-stage oxidation: Reaction conditions: the reaction temperature was controlled at 5°C; the constant voltage was 30V, the primary oxidation time was 10min, the intermittent time was 5min, the secondary oxidation reaction was 6min, the intermittent time was 5min, and the tertiary oxidation reaction was 5min; (2) Chemical deposition: Weigh: 21.4g nickel acetate, 5.2g sodium fluoride, 15g citric acid, 0.3g OP-10, add to 1L deionized water, and measure Ni +Concentration 128ppm, F - Concentration: 76ppm.
[0023] For comparison, five comparative examples are given below.
[0024] Comparative Example 1 A method for preparing a novel nickel-aluminum composite material, the process adjustment is the same as that of Example 1, except that the cleaning and activation steps of the aluminum plate are as follows: Acid pickling: At 50°C, use nitric acid aqueous solution (HNO3:H2O=1:9), ultrasonically wash for 30 seconds, then quickly transfer to pure water and rinse until neutral.
[0025] Comparative Example 2 A method for preparing a novel nickel-aluminum composite material, the process adjustment is the same as that of Example 1, except that the anodizing step is: Electrolyte: sulfuric acid aqueous solution (H2SO4:H2O=1:9); Reaction conditions: the reaction temperature was controlled at 5°C; a constant voltage of 30 V was used, and the oxidation time was 16 min.
[0026] Comparative Example 3 A method for preparing a novel nickel-aluminum composite material, the process adjustment is the same as that of Example 1, except that the multi-stage oxidation step is: Reaction conditions: the reaction temperature was controlled at 5°C; a constant voltage of 30 V was used, the primary oxidation time was 10 min, the intermittent time was 5 min, the secondary oxidation reaction was 6 min, the intermittent time was 5 min, the tertiary oxidation reaction was 5 min, the intermittent time was 5 min, and the quaternary oxidation reaction was 4 min.
[0027] Comparative Example 4 A method for preparing a novel nickel-aluminum composite material, the process adjustment is the same as that of Example 1, except that the chemical deposition step is: Weigh: 21.4g nickel acetate, add to 1L deionized water, and measure Ni + Concentration 127ppm. Weigh: 15g citric acid, 0.3g OP-10, stir evenly. Control the reaction temperature to 65℃; seal and react for 5min.
[0028] Comparative Example 5 A method for preparing a novel nickel-aluminum composite material, the process adjustment is the same as that of Example 1, except that the chemical deposition step is: Weigh: 6g nickel acetate, 6g nickel fluoride, add to 1L deionized water, measure Ni + Concentration 131ppm, F - The concentration was 84 ppm. The reaction temperature was controlled at 65°C and the reaction was sealed for 5 minutes.
[0029] According to three embodiments and five comparative examples, the experimental data are summarized and the table is as follows: From Comparative Example 1, it can be seen that pickling the workpiece with only nitric acid cannot achieve the effect of leveling the surface. The surface of the oxide film is rough and uneven, and obvious processing marks can be seen (see Figure 5 Photos in b); As shown in Comparative Example 2, a nickel-aluminum alloy can be obtained by using sulfuric acid as the electrolyte and performing a single continuous oxidation. However, the membrane prepared by this method has a large pore size, and during the continuous oxidation process, hydrogen evolution is serious. The adhesion of hydrogen causes the membrane quality to decrease, and the diameter distribution of the generated carbon nanotubes is uneven and the average size is large (see Figure 6 ); From Comparative Example 3, it can be seen that there are too many oxidation layers, the film quality is reduced, and perforation and cracking begin to appear (see Figure 5 Photos in d); As can be seen from Comparative Example 4, without adding fluorine-containing sensitizer, the nickel deposition occurs mainly on the outer surface of the porous membrane, forming a uniform nickel film (see Figure 5 In the photo e), the catalytic activity towards methane is basically lost; It can be seen from Comparative Example 5 that the nickel-aluminum alloy catalyst can be prepared without adding a carboxyl complexing agent and a surfactant, but the loading amount of active metal nickel is small and the catalytic activity for methane is reduced.
Claims
1. A method for preparing a novel nickel-aluminum composite material, characterized in that: It includes the following steps: (1) Cleaning and activation of aluminum plates: The recycled aluminum is pretreated using the process steps of "polishing-waxing-alkali washing-acid washing"; (2) Multi-stage oxidation: The activated aluminum plate pretreated in step (1) is used as the anode, and a metal plate including a nickel plate and a lead plate is used as the cathode, and a constant voltage pulse treatment is performed in an electrolyte; (3) Chemical deposition: The aluminum oxide plate prepared in step (2) is immersed in a solution containing nickel ions to perform a liquid phase chemical plating reaction: (4) The plate obtained in step (3) is subjected to an "acid expansion-alkaline stripping" treatment, and filtered and washed to neutrality to obtain a gray powder, which is then dried and calcined to obtain a nickel-aluminum composite material.
2. The method for preparing a novel nickel-aluminum composite material according to claim 1, characterized in that: In step (1), polishing: using a sanding belt and polishing paste to grind and polish the oxide film on the surface of the aluminum material; Wax removal: ultrasonic treatment of aluminum in an aqueous solution of a wax remover; Alkaline washing: adjust the pH of the aqueous solution of Na2OH, wash with ultrasound for 10 seconds, and then quickly transfer to pure water; Acid washing: At room temperature, use a mixed acid solution of phosphoric acid and nitric acid, ultrasonically wash for 30 seconds, then quickly transfer to pure water and rinse until neutral.
3. The method for preparing a novel nickel-aluminum composite material according to claim 1, characterized in that: In step (2), the electrolyte is a mixed aqueous solution of phosphoric acid and sulfuric acid, and H3PO4:H2SO4:H2O=1:4:45; reaction conditions: the reaction temperature is controlled to be 1-10°C; a constant voltage of 10-50V, an interval time of 1-20min, and a pulsed multi-stage oxidation reaction are used to achieve the effect of continuously refining the pore size of the porous layer of the oxide film during the repeated "generation-dissolution" process, and the oxidation level is controlled at 2-4 levels.
4. The method for preparing a novel nickel-aluminum composite material according to claim 1, characterized in that: In step (3), the chemical deposition solution comprises nickel ions, a fluorine-containing sensitizer, a carboxyl complexing agent, and a surfactant; the reaction conditions are: the reaction temperature is controlled to be 45-75° C.; the reaction time is 1-10 min; and the solution pH is 3-7.
5. The method for preparing a novel nickel-aluminum composite material according to claim 1, characterized in that: In step (4), the acidic pore expansion uses a 5% phosphoric acid aqueous solution at a working temperature of 10-30°C and a reaction time of 1-2 minutes; the alkaline demoulding uses an alkaline solution including NaOH and NaCO3 at a working temperature of 30-50°C and a soaking reaction time of 10-60 seconds; the gray powder is dried at 80°C for 10 hours and calcined at 400-700°C for 4 hours to obtain a nickel-aluminum composite material.
6. A method for simultaneously preparing hydrogen and carbon nanotubes using the above nickel-aluminum composite material, characterized in that: Weigh 0.01-1g of nickel-aluminum composite material as a catalyst, put it into a quartz tube, preheat it to 700°C, introduce a mixture of hydrogen and nitrogen at a rate of 10-400ml / min, react for 5-30min, introduce a mixture of methane and nitrogen at a rate of 100-1000ml / min, react for 20-60min, use gas chromatography to perform real-time online detection of the tail gas components at the end of the reactor, and calculate the methane conversion rate; The carbon nanotubes generated in the reactor are collected and the carbon nanotube generation rate is calculated.
Citation Information
Patent Citations
Catalysts for synthesizing carbon nanotubes containing amorphous α-alumina and methods for preparing carbon nanotubes using said catalysts
CN106102906B
CFAN catalyst, preparation method thereof, and application of CFAN catalyst in production of hydrogen from methane
CN110721691A
A supported methane thermal catalytic cracking catalyst and its preparation method and application
CN115364890B